Hard decision of the zero a posteriori LLR in 5G NR. Issue 2 (17th January 2020) - Wu, Hao
Abstract : The a posteriori log likelihood ratios (LLRs) have three kinds of values: negative, zero and positive. For the binary code, the hard decision is 1 when the a posteriori LLR is negative and is 0 when the a posteriori LLR is positive. To simplify the implementation of the decoder, the hard decision is usually 0 when the a posteriori LLR is zero since sign bits of zero and positive are the same. In 5G NR, this scheme increases the undetected error probability and the hard decision should be 1 when the a posteriori LLR is zero.